Systematic Error Mitigation in DORIS‐Derived Geocenter Motion. Issue 11 (8th November 2018) - Couhert, Alexandre; Mercier, Flavien; Moyard, John; Biancale, Richard
Abstract: Geocenter motion observation is one of the most demanding applications of high‐precision geodetic techniques. Here a quantitative framework is derived that shows how dominant sources of correlations and modeling issues should be mitigated when estimating the geocenter coordinates. While obtaining independent Doppler Orbitography and Radiopositioning Integrated by Satellite‐based geocenter time series, this paper shows how DORIS data and the Ocean Surface Topography Mission (OSTM)/Jason‐2 satellite can contribute to allow insight into model and geodetic technique errors and provide an independent assessment of the ITRF2014 origin stability: In particular, about ∼5mm offset along the X axis and ∼2mm higher annual amplitude in the axial direction were estimated for the geocenter coordinates over the period 2008.5–2015.5. To first order, Yarkovsky‐Schach coupling mutes Satellite Laser Ranging (SLR) + Laser Geodynamics Satellite (LAGEOS) geocenter solutions, when station heights and biases are adjusted to mitigate their modeling errors. Key Points: Independent geocenter coordinates were derived using DORIS data and the OSTM/Jason‐2 satellite Sources of correlations and modeling issues were identified and mitigated Uncertainties in the realization of the ITRF origin are addressed